The International Classification of Functioning, Disability and Health (ICF) Framework: The impact of a brief educational intervention to Chiropractic Interns - Kersley, Justyne (My University, 2015)
Introduction: The World Health Organization (WHO) encourages the use of its International Classification of Functioning, Health and Disability (ICF) framework as a biopsychosocial approach for healthcare professions to understand health and disability. The ICF framework is not currently a component of the curriculum at Canadian Memorial Chiropractic College (CMCC); however its concepts adhere to the college’s program ideals and fit well into a chiropractic model of care. Purpose: To examine whether a brief educational presentation introducing the ICF to chiropractic interns could result in a detectable change in the interns' clinical thought processes, thus stimulating the incorporation of a wider variety of ICF concepts into the interns’ report-writing including notes on progress and goal setting. Methods: This study reviewed the clinical report writing style and content of chiropractic clinical interns practicing at one of two Aptus Treatment Centres in Toronto, Ontario. Reports were analyzed prior to and following an educational intervention in which the ICF was introduced to the chiropractic clinical interns with suggestions for applications into practice. Following the intervention a subset of the chiropractic interns was specifically encouraged to incorporate ICF concepts into their report writing. Three participant groups were formed: Group 1 participants attended the presentation and received post-presentation encouragement, Group 2 participants attended the presentations but did not receive direct encouragement to incorporate ICF concepts into their report writing, Group 3 participants were current clinical interns who did not attend the presentations and consented to the evaluation of their clinical reports. After being anonymized to the researchers the pre- and post-intervention reports were reviewed using a standardized evaluation scheme that categorized the use of ICF concepts. Results: This proof of concept study provided evidence that with a brief introduction to the ICF, chiropractic interns were able to incorporate a greater variety of ICF constructs into their report writing. Detectable changes were noted with Groups 1 and 2. Group 1 demonstrated a decrease in use of references to body function and structure and a marked increase in references to both personal and environmental factors. Group 2 demonstrated a decrease in use of references to body function and structure as well as a notable increase in references to both participation and environmental factors. No detectable changes were noted in the report writing of Group 3 participants who were not exposed to the ICF teaching. Conclusions: The results of this study indicate that with even short educational presentations chiropractic interns are able to adopt a well-established framework of healthcare concepts into their patient treatment plans as noted in their report writing. This was apparent in both participant groups who attended the presentations and was not dependent on direct encouragement. This knowledge may influence the chiropractic interns’ understanding of health and disability and their interprofessional communication, and affect patient outcomes. These questions should be explored in future prospective controlled studies.
Keywords: ICF; Chiropractic